Alterations of ocular surface parameters in patients with obstructive sleep apnea syndrome - Hao, Linlin; Tian, Qingfen; Liu, Shaohua; Xu, Zhe; Yang, Lixia (Frontiers in Medicine, 2023)
Purpose This study aimed to evaluate changes in ocular surface parameters among obstructive sleep apnea syndrome (OSAS) patients. Methods 44 healthy volunteers (88 eyes) and 27 OSAS patients (54 eyes) were recruited in our cross-sectional study. 14 patients were classified as mild&moderate OSAS, and 13 patients were classified as severe OSAS. For evaluating the ocular surface, the following tests were conducted: the height of tear meniscus (TMH), first non-invasive tear break-up time (FNITBUT), mean non-invasive tear break-up time (MNITBUT), the score of Meibomian gland dropout area (Meiboscore), the tear test of anesthesia-free Schirmer I (SIT), corneal fluorescein staining (CFS), partial blinks rate (PBR), the lipid layer thickness (LLT), ocular surface disease index (OSDI). The results obtained from the study were analyzed and compared among the groups. Results FNITBUT, MNITBUT, and TMH were lower. OSDI, CFS, Meiboscore and PBR were higher in the OSAS group than those in the control group. The mild&moderate as well as the severe OSAS subgroups had statistically significantly lower TMH, and higher OSDI and PBR than the control group. Meanwhile, we found there were no significant differences between two OSAS subgroups. CFS was higher in the severe OSAS group than the mild&moderate OSAS group. Significantly lower FNITBUT, MNITBUT and higher Meiboscore were observed in the severe OSAS subgroup than in the control group, and MNITBUT was higher in severe OSAS objects than in the mild&moderate OSAS objects. LLT and SIT did not exhibit significant differences among control and OSAS subgroups. FNITBUT and MNITBUT showed significantly negative correlations with BMI, while Meiboscore showed a significant positive correlation with AHI. Conclusion Patients with OSAS have a tendence of dry eyes, whereas control subjects do not. This indicates us that the OSAS patients should pay more attention to ocular surface care.